PENGARUH SIKAP DAN TINDAKAN SISWA TERHADAP PENERAPAN PHBS DI SMP PUJA HANDAYANI - atic, Dewi Sayati; Deviliawati, Atma (Universitas Pahlawan Tuanku Tambusai, 2024)
The gap in water access in the education sector is very large. Around 80% of the community has access to drinking water services. However, in rural areas only 75% have clean drinking water. 27% of educational institutions do not have adequate sanitation and hygiene conditions and the gap in access to education remains large. Access to sanitation is greater in urban areas, but is still lacking in rural areas. The road to sanitation is still long. In urban areas, 49% have access to soap and hand washing facilities, while in rural areas, around 36% have access to soap for washing hands in clean, running water. To determine the influence of student attitudes and behavior on the implementation of PHBS at Puja Khandayani High School in 2023. Quantitative descriptive survey using a cross-sectional design. Seventh grade students (41 students) and eighth grade students (48 students) participated in this study. This sampling method amounted to 89 respondents, who were tested with a 95% confidence level using the Mann-Whitney test. The significance limit for this value is ±0.05